Pengaruh Kualifikasi Akademik dan Pengalaman Mengajar Terhadap Kinerja Guru Paud - Agilda, Nanda; Widhiasih, Angger Prima; Nurjaman, Iman (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
The performance of educators at the Early Childhood Education (ECE) level plays a vital role in determining the quality of learning for children in their formative developmental stages. This study was conducted to examine the influence of formal educational background and professional teaching experience on the work performance of ECE teachers. Employing a quantitative method with an associative approach, the study involved 65 teachers as respondents. Data were collected using a structured questionnaire and analyzed through multiple linear regression with the assistance of SPSS version 27. The results revealed that the level of formal education did not significantly contribute to improving teacher performance, as indicated by a significance value exceeding the 0.05 threshold. In contrast, teaching experience showed a statistically significant relationship with teacher performance improvement, demonstrated by a significance value below 0.05 and a positive regression coefficient. This suggests that teaching experience exerts a stronger impact on shaping teacher competence and effectiveness than academic qualifications alone. Based on these findings, it is recommended that practice-based training programs be strengthened as part of the strategy to develop ECE teacher professionalism, particularly in the Periuk District, in order to support the sustainable improvement of early childhood education services.